Kehamilan Pada Jejas Luka Sesar: Diagnosis Yang Akurat Dan Keberhasilan Dalam Tatalaksana Secara Konservatif - Purnomo, Satrio Budhi; Djanas, Dovy (Andalas Obstetrics And Gynecology Journal, 2020)
Reported case in a woman aged 30 years, with a history of cesarean scar four years ago, diagnosed with gravid two by one gravid 7-8 weeks with gestation on cesarean scar. The patient had a history of accidental trauma two days prior to the complaint of bleeding from the genitals. Several obstetricians have examined but still obtained different results (intrauterine pregnancy and ectopic pregnancy). An accurate diagnosis is critical to the success of the management of a patient with a pregnancy with this life-threatening cesarean scar. With a precise and accurate transvaginal ultrasound examination, the diagnostic criteria with ultrasound on previous surgical scars have been fulfilled in this patient, including an empty uterus, an empty cervical canal image, growth of a gestational pouch in the anterior lower segment of the uterus, and the absence of myometral image between the bladder wall and the gestational pocket. On B-HCG examination, the result was 58,808.70 mlU / mL. Conservative therapy with metrotrexate (MTX) 50 mg / m2 intramuscularly. After giving metrotrexate (MTX) therapy for four times, the results of B-HCG decreased significantly with 21.530, 12 mlU / mL, 2,949.47 mlU / mL, and 593.61 mlU / mL, respectively. After administration of metrotrexate (MTX) therapy, there was a decrease in the size of the gestational bag. Keywords: Ectopic, Pregnancy, Methotrexate, Cesarean Section